Existence of Fixed Points for An Integral Operator via Fixed Point Theorem on Gauge Spaces - Ali, Muhammad Usman; Kumam, Poom; Fahimuddin, . (Communications in Mathematics and Applications, 2018)
In this paper we have discussed the existence of fixed points for an integral operator using a new fixed point theorem in the setting of gauge spaces.